Validating the model of predictors of academic self-handicapping behavior - Mwita, Hafsa Mzee; Nordin, Mohamad Sahari; Ibrahim, Mohd Burhan (Springer, 2013)
The main aim of the present study is to validate the model of predictors of self-handicapping behavior (POASH) on the data derived from undergraduate students in an ongoing co-curriculum compulsory course. The study adapted and extended the original theory of reciprocal interaction of emotion, cognition and behavior by adding self-handicapping behavior component. In so doing, this study assessed the direct and indirect effects of emotion, cognition and behavior via student engagement on self-handicapping behavior. The second purpose of the study is to evaluate gender and nationality status invariants of the causal structure of POASH. This cross-validation procedure determined whether gender and nationality status moderated the causal structure of the model, and thus the generality of POASH. The data was collected from two self-reported questionnaires administered to 790 undergraduates of an International Islamic University in Malaysia. A confirmatory three-step approach theory testing and development using Maximum Likelihood method was applied. The results of structured equation modeling supported the adequacy of POASH and the causal structure of POASH proved to be applicable to both genders and nationality statuses.